Direct and indirect effects of pesticides on a benthic grazer during its life cycle - Marcus Rybicki; Dirk Jungmann (Environmental Sciences Europe, 2018)
Abstract Background Macroinvertebrates in aquatic ecosystems are repeatedly exposed to pesticides during their life cycle. Effects of consecutive exposure during different life stages and possible synergistic effects are not addressed in the standardized hazard assessment. The present study investigated two environmentally relevant exposure scenarios in batch (microcosm) and artificial indoor stream (mesocosm) experiments using the larvae of the mayfly Rhithrogena semicolorata (grazer) and natural aufwuchs. Grazers were analysed regarding growth, physiological condition, and drift behaviour, while the aufwuchs was analysed in terms of biomass using the particulate organic carbon as well as the chlorophyll a content. The aim was to reveal direct and indirect effects of an herbicide exposure during autumn on juvenile grazers and an insecticide exposure during spring on semi-juvenile grazers. Results Direct and indirect effects were found in both exposure scenarios at environmentally relevant concentrations. In the herbicide exposure scenario with terbutryn, clear direct effects on the aufwuchs community with a LOEC of 0.38 µg L−1 were found. Effect levels of grazers due to indirect effects were equal, with the overnight drift being the most sensitive grazer endpoint. In the insecticide exposure scenario, clear lethal and sub lethal effects of lambda-cyhalothrin were evident. Derived LC50 values for the artificial indoor stream and batch experiment were 2.42 µg g−1 OC (69 days) and 1.2 µg g−1 OC (28 days), respectively. Sub lethal effects in terms of increased drift as well-reduced growth and triglyceride levels were found at concentrations of 1.4 and 0.09 µg g−1 OC (LOECs). These results were confirmed by the batch experiment, which revealed effect values in the similar range. Finally, a clear indirect effect of the insecticide on the aufwuchs was evident in the batch experiment with an LOEC at 0.9 µg g−1 OC. Conclusion Toxicity Exposure Ratios calculated with the derived effect values indicate a risk for the investigated grazer by both pesticides. Moreover, observed indirect effects during the herbicide exposure seem to be able to affect the grazers during a second exposure with an insecticide, due to reduced physiological conditions. We suggest further research with time-shifted exposure scenarios to gain a better understanding of the complex interactions of pesticides with the life cycle and the food webs of macroinvertebrates.